Nannie Helen Burroughs: Lamplighter of the Impossible - LAKRISTA L PAGE (Adult Education Research Conference, 2016)
Adult Facilitators have limited resources highlighting exceptional Black women of our disciple. The purpose of this historical analysis will uncover why Nannie Helen Burroughs was ostracized by the Black intellectuals.
Keywords: Black women; Adult Education History; Leadership; Race; Class and Gender; and Inner Culture Marginalization